1998
DOI: 10.1007/pl00006384
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Measures of Synonymous Codon Usage Bias

Abstract: Synonymous codons are not generally used at equal frequencies, and this trend is observed for most genes and organisms. Several methods have been proposed and used to estimate the degree of the nonrandom use of the different synonymous codons. The estimates obtained by these methods, however, show different levels of both precision and dispersion when coding regions of a finite number of codons are under analysis. Here, we present a study, based on computer simulation, of how the different methods proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
217
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(222 citation statements)
references
References 20 publications
5
217
0
Order By: Relevance
“…The minimal number of differences found between males and females coupled with the individual variation already observed suggests that the differences are unlikely to represent expression of alternative genes. Furthermore, sequence polymorphism is a well described phenomenon in Drosophila XDH (32)(33)(34). Multiplicity of AOX genes has been established for some organisms (19 -24), and in plants these data are supported by multiple cDNA sequences of approximately 80% identity (19,20).…”
Section: Table III Quantitation Of Rna Hybridizationmentioning
confidence: 99%
“…The minimal number of differences found between males and females coupled with the individual variation already observed suggests that the differences are unlikely to represent expression of alternative genes. Furthermore, sequence polymorphism is a well described phenomenon in Drosophila XDH (32)(33)(34). Multiplicity of AOX genes has been established for some organisms (19 -24), and in plants these data are supported by multiple cDNA sequences of approximately 80% identity (19,20).…”
Section: Table III Quantitation Of Rna Hybridizationmentioning
confidence: 99%
“…This relative difference in the frequency of event for each codon is called codon bias. The codon usage table for a species Homo sapiens and E. coli gives the codon bias information for that species (27). To date, the heterologous gene expression is applied as a fundamental methodology in biological process with some restrictions in implementation (33).…”
Section: Discussionmentioning
confidence: 99%
“…MN002309.3) which was optimized for fully expression in E. coli. Genetic codons of amino acids coded by more than one codon were changed to synonymous codons commonly used by E. coli (27). The optimized sequence was chemically synthesized and inserted in to the expression vector pET-28a (+) with BamHI and XbaI restriction sites (Generay Biotech Co., Ltd).…”
Section: Constructing Expression Vector Of Pet-28a (+)-Hlifmentioning
confidence: 99%
“…A phenomenon designated codon usage bias (1)(2)(3). Codon usage bias among synonymous codons has been documented for numerous genes in variant species (3)(4)(5)(6)(7)(8)(9). It is reported that synonymous codon usage bias may be connected with different biological factors (6,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%